Древнейшие полевки трибы Micritini (Rodentia, Microtidae) юга УССР - Топачевский, В.А.; Скорик, А.Ф.; Рековец, Л.И. (Вестник зоологии, 1978)
The article deals with a description of the new species of the Early-Pliocene vole of the lschymomys genus from the tops of the Baltian suite (problematic analogs of the continental Pontian) in the Kuchurgan river valley (neat vil. Frunzovka, Frunzovkian District, Odessa Region). Findings of this genus representatives previously known from analogs of the Pavlodarian suite in Western Siberia and Kazakhstan are given first for Eastern Europe. I. ponticus sp. n. differs distinctly from the typical species I. quadriradicatus Zazigin by almost complete dissociation of the middle pair of enamel loops (parakon and hypokon) M³ as well as by a stronger development of tracks and counter on M₁. The Frunzovkian faunistic complex of mammals is distinguished for the first time. It reflects, according to its qualitative specificity, the almost unstudied until recently Early Pliocene stage in history of the continental mammals faunas from the South of the USSR European section if only in its late completing phase of development. Species composilion of the complex reflects the usual rapid settling of the Asian steppe and semi-desert forms to the territory of Eastern Europe.